Maternal mortality in the context of political free health care on pregnancy and birth to the Treichville teaching hospital, Abidjan-Côte d’Ivoire - Yao, Ignace N’guessan; Guié, Privat Yéret; Lamine Dia, Jean-Marc; Kouamé Bohoussou, Paul-Eric; N’guessan, Edouard Konan; Saki, Corneille Téa; Anongba, Simplice Danho (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Maternal mortality continues to be a drama in the countries of Sub Saharan Africa. Despite the efforts of the world through the millennium development goals (MDGs) 5 and 6, the situation remains very worrying in this region. If in developed countries, maternal mortality is an indicator of the quality of obstetric care, for poor countries, it is an indicator of social and economic development. Methods: Our study was designed to assess the impact of free support of pregnancy and childbirth on maternal mortality at treichville teaching hospital in Abidjan. We conducted a retrospective descriptive study of deaths of our service over the period September 2012 to August 2013 taking into account the hospital data. Results: During this period, we recorded 32 deaths per 3173 live births. Eight out of ten patients were younger than 35 years. And half had no education. 93.75% of patients were evacuated to another structure and more than half of the deaths occurred less than two hours after admission to our service. Bleeding causes dominate with 37.50% of postpartum haemorrhage. Conclusions: Maternal death rates in our service remain high despite the policy of free care and factors of this mortality remain unchanged for decades.